Nonfamilial cherubism in a 6-month-old infant: a case report - Seyedeh Sedigheh Hamzavi; Alireza Askari; Rosemina Bahrololoom; Maral Mokhtari; Anahita Sanaei Dashti; Fatemeh Yarmahmoodi; Somaye Rashidi (BMC, 2024)
Abstract Background Cherubism is known as a very rare autosomal dominant familial disorder of childhood caused by a mutation in the SH3BP2 gene on 4p16.3. It has not yet been observed at birth and is usually diagnosed in children aged 2-7. Here, we present a non-hereditary case of cherubism at a very early age. Case presentation A 6-month-old girl presented with bilateral progressive jaw enlargement. On physical examination, bilateral asymmetrical jaw enlargement, predominantly on the left side, and some enlarged, non-tender, mobile submandibular lymph nodes were detected. No other abnormality was observed. Further investigations with radiology suggested cherubism and Burkitt's lymphoma as differential diagnoses. Later on, histopathologic evaluations were suggestive of cherubism. No surgical interventions were indicated, and the child is on regular follow-ups. Conclusion Non-hereditary Cherubism, despite scarcity, can present in children below two years of age, even as early as the beginning of primary dentition. Accurate and swift diagnosis is essential to avert physical and psychological complications. Our case report shows the importance of keeping cherubism in mind as a differential diagnosis of bone disease, even in children under a year old, and the value of interdisciplinary collaboration in dealing with rare genetic disorders.